The Use Of Face Book As An Interactive Multimedia For Teaching Basic Writing To The First Graders In Educational Program Of Kidergarten Teacher IKIP Veteran Semarang - Ratno, Ratno (PAWIYATAN, 2015)
ÃÂ This research was conducted to describe the use of face book to improve the simple writing skill to the first graders in Educational Program of Kindergarten Teacher IKIP Veteran Semarang in academic year of 2014/2015 and to find out the result of applying face book for teaching simple writing. The data source of my study was the first graders in Educational Program of Kindergarten Teacher IKIP Veteran Semarang in academic year of 2014/2015 which consists of 35 students. The instruments consist of a free writing test. It means that the student were free to choose any topic of their experience because it is in the form of a simple writing text. This study is an action research. There were four steps in conducting an action research: Planning. Action, Observation, and Reflection. This action research was done in two cycles. The teaching of simple structure through face book contributes significantly to the studentsÃ¢â¬â¢ improvement. There were 63.31 on pre test and 78.60 on post test of improvements of writing text. Based on this result, I could draw conclusion that the use of face book can improve the studentÃ¢â¬â¢s writing skill.ÃÂ Keywords: Face book, Improve, Interactive Multimedia, Writing skill.